Cultural capital in the dimension of community tourism described through Stories, legends, local history and community way of life - Srithon, Atsadawoot; Tularak, Umarin (Academic and Research Journal of Liberal Arts (Online), 2021)
This research studies Storytelling and rituals in Phu Wiang mountain community, Wiang Kao district, Khon Kaen province by conducting a site visit. For myths, data are collected from data providers in a word of Telling network in order to study myths both in oral and written foams. For rituals, participant observation and non-participant observation are employed in ordered to be used as a database for analyzing cultural interpretation and for constructing cultural capital for tourism support in various dimensions. From the study, it was found that the community used cultural capital to promote tourism in order to strengthen the community from identity to community business. Tourism is supported by tales, legends, local history. and the way of life of the community can be classified into 7 dimensions as follows: 1) Agritourism 2) Ecotourism 3) Cultural Tourism 4) Health Tourism 5) Business Tourism 6) Ecotourism 7) Buddhist Tourism generate income and create a sustainable economic base by local people in the community resulting in a creative way of presenting tourism in different dimensions.